PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP LOYALITAS PELANGGAN MENGGUNAKAN E-WALLET (GOPAY) MILIK PT GOJEK INDONESIA (Penelitian pada pengguna layanan Gopay pada aplikasi Gojek di Jakarta Selatan) - Astri Nurhidayah (2021)
This research is a quantitative research, and the author uses a descriptive method to implement Gopay services. The population selected in this survey are Gopay service users located in South Jakarta. The purpose of this study is to show whether customer loyalty to Gopay services is influenced by brand image and brand trust variables. The sampling method chosen is non-probability sampling, and the type is purpose sampling. The source of data in this survey was obtained by distributing the survey to 100 respondents. The analytical tool used to support this research is SmartPLS 3.0. Furthermore, the results of this study are (1) brand image has a significant effect on customer loyalty (2) brand trust has a significant effect on customer loyalty